Pet’s influence on humans’ daily physical activity and mental health: a meta-analysis - Martins, Catarina F.; Soares, Jorge P.; Cortinhas, António; Silva, Luís; Cardoso, Luís; Pires, Maria A.; Mota, Maria P. (Frontiers in Public Health, 2023)
The benefits of the human-animal bond on owners' health and quality of life have been the focus of research in recent decades. However, the results are still inconsistent. Thus, this study aims to investigate whether the presence of a pet, compared to a control group, influences daily physical activity levels and mental health using a meta-analytic method. Methods: The PubMed, Web of Science, and Scopus databases were searched for all research articles that included pets as an object of study and related mental health and quality of life variables between pet owners and non-owners until April 2022. The PRISMA 2020 checklist was used, and the Downs and Back checklist was used to assess the methodological quality of the studies. Standardized mean differences and 95% confidence intervals were used to assess the difference between a group of pet owners and non-pet owners. Results: An initial search located 11,389 studies, but only 49 studies fulfilled all requirements. Our results indicate that pets have a moderately significant positive effect on the physical activity of owners compared to non-pet owners. Among the moderating variables, the frequency of physical activity showed a highly significant effect, indicating that owners had a higher frequency of physical activity than non-owners. Moreover, our results indicate a significant impact but with a low effect size of pets on owners' mental health when compared to non-pet owners. Conclusion: Pet ownership does not seem to influence owners' mental health, but it does influence their physical activity. Specifically, owners show a higher frequency of physical activity than non-owners.